Predator–prey interaction in insects and arachnids: a chemical ecology perspective - Vivek Kempraj; Soo Jean Park (Academia Environmental Sciences and Sustainability)
Animals emit distinctive semiochemicals—chemical substances that mediate interactions between organisms—and many of them have evolved means to detect and respond to these chemicals emitted by others. This results in a complex web of semiochemical-mediated interactions that are as diverse as the number of species involved. The interactions between predators and prey play out both in the present and through evolutionary time. Predators are selected to become proficient at detecting and catching prey. Concurrently, there is a selection on prey to become efficient at detecting and eluding predators. Predator–prey interaction has sequential stages starting with initial detection, attack by the predator or either evasion or counterattack by the prey, capture by the predator or escape by the prey, and ingestion by the predator or alarm by the prey. At each stage of the predator–prey interaction sequence, stage-specific semiochemicals may be released by both the predator and the prey. Despite the numerous studies of predator–prey interactions, there is surprisingly little information available about the semiochemicals that mediate predator–prey interactions in insects and arachnids. Most work has been limited to bioassays that demonstrate or suggest the presence and biological role of semiochemicals, but in the large majority of cases, the chemical composition of semiochemicals remains unstudied. Here, we attempt to discuss evidence of predator- or prey-produced semiochemicals that induce or prime a predatory or anti-predatory behavior in terrestrial insects and arachnids, and the potential for developing these biologically active compounds as pest management tools.